A location list of literary archives in Brazil. Issue 1 (November 2018) - Negrini, Luciana; Sutton, David
Abstract : Brazil has a long tradition of collecting literary archives, in a wide range of institutions. This listing, by author and location, of almost 150 such collections demonstrates the richness of the country's literary archival heritage.